2021
DOI: 10.37213/cjal.2021.31319
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Engagement in Task-based Synchronous Computer Mediated Interaction

Abstract: Investigating task-based synchronous computer-mediated communication (SCMC) interaction has increasingly received scholarly attention. However, studies have focused on negotiation of meaning and the quantity, focus and resolution of language related episodes (LREs). This study aims to broaden our understanding of the role of audio, video, and text SCMC conditions by additionally examining second language (L2) learners’ levels of engagement during the production of LREs as a result of interactive real-world tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…More recently, other studies researching interactions and LREs have incorporated audio (Bueno-Alastuey, 2011, 2013Yanguas, 2012), and only very recently, a few of them have also included video interactions (Akiyama, 2014;Akiyama & Saito, 2016;Monteiro, 2014;Saito & Akiyama, 2017;Strawbridge, 2021;Van der Zwaard & Bannink, 2014Yanguas & Bergin, 2018). Several of these studies are still aimed at comparing the specificities of these settings for the affordances they bring to focus on form in otherwise meaning-related tasks or interactions, either between FTF and audio-and video-based SCMC (Bueno-Alastuey, 2011;Loewen & Isbell, 2017;Yanguas, 2010), or between text-based and audio-based SCMC ( Van der Zwaard & Bannink, 2014;Torres & Yanguas, 2021;Yanguas, 2010Yanguas, , 2012. Yanguas (2010 and2012) made a three-way comparison between FTF, video-and audio-SCMC task-based interactions and found that turn-taking in FTF and video-based SCMC were very similar and both differed from the interactional patterns found in audio-based SCMC.…”
Section: Interaction In Scmc: Negotiation Of Meaning and Formmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, other studies researching interactions and LREs have incorporated audio (Bueno-Alastuey, 2011, 2013Yanguas, 2012), and only very recently, a few of them have also included video interactions (Akiyama, 2014;Akiyama & Saito, 2016;Monteiro, 2014;Saito & Akiyama, 2017;Strawbridge, 2021;Van der Zwaard & Bannink, 2014Yanguas & Bergin, 2018). Several of these studies are still aimed at comparing the specificities of these settings for the affordances they bring to focus on form in otherwise meaning-related tasks or interactions, either between FTF and audio-and video-based SCMC (Bueno-Alastuey, 2011;Loewen & Isbell, 2017;Yanguas, 2010), or between text-based and audio-based SCMC ( Van der Zwaard & Bannink, 2014;Torres & Yanguas, 2021;Yanguas, 2010Yanguas, , 2012. Yanguas (2010 and2012) made a three-way comparison between FTF, video-and audio-SCMC task-based interactions and found that turn-taking in FTF and video-based SCMC were very similar and both differed from the interactional patterns found in audio-based SCMC.…”
Section: Interaction In Scmc: Negotiation Of Meaning and Formmentioning
confidence: 99%
“…Yanguas (2010 and2012) made a three-way comparison between FTF, video-and audio-SCMC task-based interactions and found that turn-taking in FTF and video-based SCMC were very similar and both differed from the interactional patterns found in audio-based SCMC. Audio-based interactions lacked visual cues which translated into a higher number of negotiation turns and longer-term comprehension gains regarding vocabulary acquisition (Yanguas, 2012) and increased learner engagement (Torres & Yanguas, 2021). Bueno-Alastuey (2011) found that the audio-SCMC group outperformed the FTF one in post-test scores and task achievement.…”
Section: Interaction In Scmc: Negotiation Of Meaning and Formmentioning
confidence: 99%